Evaluation of the Accreditation Program for Pancasila Ideology Development Training Organizers with an ApproachAssessment Evaluability and Performance Monitoring (AEPM) - Nurcahya, Fikri; Badrujaman, Aip; Priyanto, Sugeng; Madani, Faisal (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to evaluate the implementation of the accreditation program for Pancasila Ideology Education and Training (Diklat PIP) providers conducted by BPIP. The evaluation employs the AEPM model, which analyzes four key dimensions: Context, Input, Activity, and Performance Monitoring. Data were collected from 46 respondents representing accredited institutions through a closed-ended Likert-scale questionnaire. Descriptive analysis shows that the Context and Input dimensions received the highest scores, indicating strengths in program planning and institutional readiness. Conversely, the Performance Monitoring dimension obtained the lowest score, highlighting weaknesses in the sustainability of implementation and post-accreditation follow-up. Spearman correlation analysis reveals significant positive relationships among the dimensions, with the highest correlation observed between Context and Input (r = 0.795). These findings suggest that program success largely depends on the integration of design, implementation, and monitoring aspects. The study concludes that although the accreditation has progressed well in administrative terms, the substantive transformation toward sustainable implementation of Diklat PIP still requires further reinforcement. It recommends reform in post-accreditation monitoring and future research using a mixed-method approach to enrich program evaluation holistically.